High-rate and high-first-effect biomass hard carbon composite negative electrode material as well as preparation method and application of high-rate and high-first-effect biomass hard carbon composite negative electrode material
Through low-temperature pretreatment of biomass raw materials and phosphoric acid and graphene, a core-inner shell-shell structure is formed, which solves the problem of poor efficiency and rate performance of biomass hard carbon anode material in the first week in sodium ion batteries, achieving high Efficiency and electrochemical properties for long cycle life.
Patent Information
- Application Number
- CN202411636783.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing biomass hard carbon anode material has low efficiency and poor rate performance in sodium ion batteries in the first week, making it difficult to achieve high efficiency and excellent cycle life at the same time.
By mixing biomass raw materials with phosphoric acid and heating, the low-temperature pre-carbonization is carried out, and the coating treatment of graphene and transition metal salts is combined to form a core-inner shell-out shell structure. Graphene and carbon nanotubes grow together at high temperatures, enhancing the packaging The chemical bond between the coating and hard carbon improves cycling performance, and broadens the spacing of the hard carbon layer through phosphorus doping to improve sodium ion embedding/detachment kinetics.
It has achieved high first-time Coulomb efficiency, excellent rate performance and long cycle life, and overcomes the shortcomings of difficult to improve the first-week Coulomb efficiency and rate performance in the prior art.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for sodium ion batteries, and in particular to a high-rate, high-initial-effect biomass hard-carbon composite negative electrode material, and a preparation method and application thereof. Background Art
[0002] With the rapid development of the electric vehicle market, the demand for lithium-ion batteries has also surged. However, the reserves of lithium resources in the earth's crust are limited, which has caused the cost of lithium-ion batteries to remain high. At the same time, sodium-ion batteries work in a similar way to lithium-ion batteries, have an energy density close to that of lithium-ion batteries, and have abundant reserves, uniform distribution, and low cost. They are expected to be used in large-scale energy storage devices.
[0003] Hard carbon is the most commonly used negative electrode material for commercial sodium-ion batteries. At present, there are two main raw materials for hard carbon materials, petroleum coal and biomass. Petroleum coal materials are widely available, and the prepared hard carbon has stable performance and high carbon yield, but due to its structural characteristics, its specific capacity is lower than other materials; and biomass as a carbon source has become the focus of attention for the preparation of hard carbon materials due to its environmental friendliness and low cost. However, the currently commonly used biomass hard carbon negative electrode has low first-cycle coulombic efficiency (<70%) and poor rate performance, which hinders its commercial application. Therefore, the development of hard carbon materials with high first-cycle coulombic efficiency and high rate performance is the current research and development focus and hot spot of sodium-ion batteries.
[0004] At present, many strategies have been proposed to improve the first-cycle coulombic efficiency and rate performance of hard carbon, but it is difficult to achieve these two goals at the same time. Designing structures with large specific surface areas or doping with heteroatoms are common methods to improve the rate performance of hard carbon. However, hard carbon materials with structures with large specific surface areas or doped with heteroatoms will lead to lower first-cycle coulombic efficiency. In contrast, hard carbon materials with low defects and low specific surface areas can achieve high first-cycle coulombic efficiency but cannot improve sodium storage kinetics. Therefore, it is still necessary to explore effective methods to simultaneously achieve high first-cycle coulombic efficiency and excellent rate performance. Summary of the invention
[0005] In view of the shortcomings of the prior art mentioned above, the object of the present invention is to provide a high-rate, high-first-effect biomass hard-carbon composite negative electrode material that can take into account excellent first-cycle coulombic efficiency, rate performance and long cycle life. At the same time, the present invention will also provide a method for preparing the hard-carbon composite negative electrode material; in addition, the present invention will also provide the use of the hard-carbon composite negative electrode material.
[0006] To achieve the above objectives and other related objectives, the present invention provides the following technical solutions: The first aspect of the present invention provides a method for preparing a high-rate and high-initial-effective biomass hard carbon composite negative electrode material, comprising the following steps: (1) After the biomass raw material and phosphoric acid are uniformly mixed, they are heated to react for a period of time, and then crushed and sieved to obtain a P-doped precursor; (2) pre-carbonizing the P-doped precursor of step (1), cooling it to room temperature, and pulverizing it to obtain a P-doped pre-carbonized precursor; (3) mixing graphene with water and performing ultrasonic dispersion to obtain a graphene dispersion; (4) transferring the graphene dispersion of step (3) into a constant temperature water bath, adding a P-doped pre-carbonized precursor and a transition metal salt to obtain a suspension, filtering, washing, and drying the suspension to obtain a graphene-coated P-doped pre-carbonized precursor; (5) chemically vapor depositing the graphene-coated P-doped pre-carbonized precursor of step (4) with a carbon source to obtain material 1; (6) placing the material 1 of step (5) in a high temperature furnace for high temperature carbonization treatment, and cooling to room temperature to obtain material 2; (7) The material 2 obtained in step (6) is soaked in an acid solution, and finally washed with deionized water until it is neutral and dried to obtain the hard carbon composite negative electrode material.
[0007] In step (1) and step (2), after the biomass raw material and phosphoric acid are mixed, they are heated and pre-carbonized at low temperature so that the phosphorus atoms are inserted into the interlayer spacing of the hard carbon precursor to obtain a P-doped hard carbon precursor (i.e., a P-doped pre-carbonized precursor). In step (3) and step (4), graphene that can be uniformly dispersed in water is mixed with a transition metal salt and a P-doped hard carbon precursor. During the mixing process, the graphene can be uniformly coated on the surface of the P-doped hard carbon precursor, and the transition metal ions can be uniformly attached to the graphene surface and uniformly dispersed inside the P-doped hard carbon precursor. Subsequently, in the chemical vapor deposition process of step (5), the carbon source grows carbon nanotubes in situ on the graphene surface under the catalytic action of the transition metal ions, thereby forming a core-inner shell-outer shell structure. In the high-temperature carbonization process of step (6), the graphene and its surface The transition metals on the surface synergistically induce the hard carbon to grow along the graphene layer, enhance the chemical bond between the coating layer and the hard carbon, and make the coating layer tightly coated on the hard carbon surface. Finally, graphene and carbon nanotubes form a three-dimensional network coating layer with high elasticity and high stiffness on the hard carbon surface, which improves the cycle performance of the composite material. The transition metal ions on the surface of the coating layer can also catalyze graphitization to generate a more regular and ordered graphite-like microcrystalline structure coating layer, reduce the defects of graphene and carbon nanotubes, and improve the first coulomb efficiency of the composite material. In the high-temperature carbonization process, graphene, carbon nanotubes and metal ions catalyze graphitization to generate graphite crystals inside the hard carbon, which improves the electron transfer kinetics. At the same time, phosphorus doping broadens the interlayer spacing of the hard carbon and improves the sodium ion embedding / ejection kinetics. The synergistic improvement of ion transfer and electron transfer ensures good rate performance.
[0008] As a preferred embodiment of the present invention, in step (1), the biomass raw material includes at least one of lychee wood, apple wood, poplar wood, bamboo, fruit shell, straw, coconut shell and corn cob.
[0009] As a preferred embodiment of the present invention, in step (1), the mass ratio of the phosphoric acid to the biomass raw material is (5-20):100.
[0010] As a preferred embodiment of the present invention, in step (1), the biomass raw material and phosphoric acid are mixed and then heated to 150°C-200°C for reaction for 1-6 hours.
[0011] As a preferred embodiment of the present invention, in step (2), the pre-carbonization treatment is: pre-carbonizing the P-doped precursor at 300° C.-600° C. for 1-6 h in a nitrogen atmosphere.
[0012] As a preferred embodiment of the present invention, in step (3), the graphene includes at least one of sulfonated graphene and graphene oxide. The source of the graphene is not particularly defined, and can be prepared by methods known in the art or purchased through commercial channels.
[0013] As a preferred embodiment of the present invention, in step (3), the mass of graphene added per milliliter of water is (1-1.5) mg; for example, 1 mg, 1.1 mg, 1.2 mg, 1.3 mg, 1.4 mg or 1.5 mg.
[0014] As a preferred embodiment of the present invention, in step (3), the power and time of ultrasound are not particularly limited, as long as the graphene can be evenly dispersed. Exemplarily, the graphene is mixed with water and ultrasonically dispersed for 1-10 hours to obtain a graphene dispersion.
[0015] As a preferred embodiment of the present invention, in step (4), the temperature of the constant temperature water bath is 80-95°C; for example, 80°C, 85°C, 90°C or 95°C.
[0016] As a preferred embodiment of the present invention, in step (4), the P-doped pre-carbonized precursor and transition metal salt are added to the graphene dispersion under stirring conditions.
[0017] As a preferred embodiment of the present invention, in step (4), the mass ratio of the graphene to the P-doped pre-carbonized precursor is (0.1-0.4):100; for example, 0.1:100, 0.2:100, 0.3:100 or 0.4:100.
[0018] As a preferred embodiment of the present invention, in step (4), the transition metal salt includes at least one of nitrates, chlorides, sulfates, acetates and oxalates of transition metals; and the transition metal is at least one of iron, cobalt, nickel and chromium.
[0019] Since the P-doped pre-carbonized precursor is rich in micropores, after step (4), transition metal ions are evenly distributed in the graphene coating layer and the P-doped pre-carbonized precursor.
[0020] As a preferred embodiment of the present invention, in step (4), the mass ratio of the transition metal salt to the P-doped pre-carbonized precursor is (1-5):100; for example, 1:100, 2:100, 3:100, 4:100 or 5:100.
[0021] As a preferred embodiment of the present invention, in step (4), filtration is performed by methods known in the art, such as suction filtration, centrifugal filtration, etc.; washing is performed by methods known in the art, such as washing with deionized water.
[0022] As a preferred embodiment of the present invention, in step (4), the drying temperature is 80-100°C.
[0023] As a preferred embodiment of the present invention, in step (5), the carbon source includes at least one of acetylene, ethylene, methane, ethane, propane and n-butane.
[0024] As a preferred embodiment of the present invention, in step (5), the chemical vapor deposition is carried out under the protection of an inert atmosphere, and the inert atmosphere is selected from a nitrogen atmosphere or an argon atmosphere.
[0025] As a preferred embodiment of the present invention, in step (5), the flow rate of the carbon source is not limited and can be adjusted according to actual conditions to satisfy the volume ratio of the carbon source to the inert atmosphere of (1-5):(50-100).
[0026] As a preferred embodiment of the present invention, in step (5), the temperature of the chemical vapor deposition is 500-800°C; for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C. The time of the chemical vapor deposition is 1-6 hours; for example, 2-5 hours; preferably 4 hours or 6 hours. Further, after the chemical vapor deposition process is completed, the obtained product is subjected to a natural cooling process.
[0027] As a preferred embodiment of the present invention, in step (6), the high temperature carbonization treatment is as follows: placing the material 1 in a high temperature furnace and carbonizing it at 900°C-1400°C for 1-6 hours in a nitrogen atmosphere.
[0028] As a preferred embodiment of the present invention, in step (7), the acid of the acid solution is selected from at least one of hydrochloric acid, sulfuric acid, nitric acid and hydrofluoric acid.
[0029] As a preferred embodiment of the present invention, in step (7), the pH of the acid solution is 3-4.
[0030] The second aspect of the present invention provides a high-rate, high-initial-effect biomass hard carbon composite negative electrode material prepared by the above-mentioned preparation method, wherein the hard carbon composite negative electrode material has a core-shell structure, wherein the core-shell structure comprises a core, an inner shell and an outer shell, wherein the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell; the core comprises biomass hard carbon containing P and graphite crystals, the inner shell comprises graphene, and the outer shell comprises carbon nanotubes.
[0031] Furthermore, the thickness of the shell is 5nm-10nm; for example, 5nm, 6nm, 7nm, 8nm, 9nm or 10nm.
[0032] Furthermore, the thickness of the inner shell is 10 nm-25 nm; for example, 10 nm, 15 nm, 20 nm or 25 nm.
[0033] The third aspect of the present invention provides a use of the above-mentioned high-rate, high-initial-effective biomass hard carbon composite negative electrode material, which is used in sodium ion batteries; preferably used to prepare the negative electrode of a sodium ion battery.
[0034] A fourth aspect of the present invention provides a negative electrode for a sodium ion battery, wherein the negative electrode comprises the above-mentioned high-rate, high-initial-effective biomass hard-carbon composite negative electrode material.
[0035] As described above, the high-rate, high-initial-effect biomass hard carbon composite negative electrode material of the present invention and its preparation method and application have the following beneficial effects: The present invention mixes biomass raw materials and phosphoric acid, and then heats and pre-carbonizes them at low temperature to insert phosphorus atoms into the interlayer spacing of the hard carbon precursor to obtain a P-doped hard carbon precursor; graphene that can be evenly dispersed in water is mixed with a transition metal salt and the P-doped hard carbon precursor. During the mixing process, the graphene can be evenly coated on the surface of the P-doped hard carbon precursor, and the transition metal ions can be evenly attached to the graphene surface and evenly dispersed inside the P-doped hard carbon precursor; then, during the chemical vapor deposition process, the carbon source grows carbon nanotubes in situ on the graphene surface under the catalytic action of the transition metal ions. During the high-temperature carbonization process, On the one hand, the graphene coating layer and the transition metal on its surface synergistically induce the hard carbon to grow along the graphene layer, enhancing the chemical bond between the graphene coating layer and the hard carbon, so that the graphene coating layer is tightly coated on the hard carbon surface. Finally, the graphene and carbon nanotubes form a three-dimensional network coating layer with high elasticity and high rigidity on the hard carbon surface, which effectively improves the cycle performance of the hard carbon composite negative electrode material. On the other hand, the transition metal ions on the surface of the graphene coating layer can catalyze graphitization to generate a more regular and orderly graphite-like microcrystalline structure coating layer, which reduces the defects of graphene and carbon nanotubes, improves the first coulomb efficiency of the composite negative electrode material, and solves the problem of reduced first-cycle coulomb efficiency caused by P atom doping while increasing the rate. On the other hand, phosphorus doping can widen the interlayer spacing of hard carbon and improve the insertion / extraction kinetics of sodium ions; graphene, carbon nanotubes and metal ions catalyze graphitization to generate graphite crystals inside the hard carbon, which improves the electron transfer kinetics; the synergistic improvement of ion transfer and electron transfer ensures good rate performance. DETAILED DESCRIPTION
[0036] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0037] Example 1 A high-rate, high-initial-effect biomass hard-carbon composite negative electrode material, the preparation method of which comprises the following steps: (1) 100 g of fruit shell and 15 g of phosphoric acid were mixed evenly, heated to 160 °C for 4 h, and crushed and sieved to obtain a P-doped precursor; (2) pre-carbonizing the P-doped precursor obtained in step (1) at 500° C. for 2 h in a nitrogen atmosphere, cooling it to room temperature, and pulverizing it to obtain a P-doped pre-carbonized precursor; (3) mixing 1.2 g of sulfonated graphene with 1 liter of water and performing ultrasonic dispersion for 4 hours to obtain a sulfonated graphene dispersion; (4) The sulfonated graphene dispersion of step (3) was transferred to a constant temperature water bath at 85° C., 1000 g of P-doped pre-carbonized precursor was added during stirring, 30 g of ferric nitrate was added after stirring for 6 hours, and stirring was continued for 2 hours to obtain a suspension, and the suspension was filtered, washed with pure water, and dried to obtain a graphene-coated P-doped pre-carbonized precursor; (5) placing the graphene-coated P-doped pre-carbonized precursor of step (4) in a rotary kiln, and introducing acetylene at a flow rate of 1 L / min for 6 hours in a nitrogen atmosphere at a flow rate of 100 L / min and an environment of 600° C. to generate carbon nanotubes, then switching to introducing nitrogen, and naturally cooling to room temperature to obtain material 1; (6) Material 1 is placed in a high-temperature furnace and carbonized at 1200°C for 5 h under a nitrogen atmosphere. After cooling to room temperature, material 2 is obtained; (7) Material 2 was soaked in a hydrochloric acid solution with a pH of 3 for 1 hour, and finally washed with deionized water until neutral and dried to obtain the hard carbon composite negative electrode material.
[0038] The prepared hard carbon composite negative electrode material has a core-shell structure, which includes a core, an inner shell and an outer shell, wherein the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell, wherein the core is hard carbon containing P and graphite microcrystals, the inner shell is graphene, and the outer shell is carbon nanotubes. The thickness of the outer shell is 6 nm, and the thickness of the inner shell is 22 nm.
[0039] Example 2 A high-rate, high-initial-effect biomass hard-carbon composite negative electrode material, the preparation method of which comprises the following steps: (1) 100 g coconut shell and 10 g phosphoric acid were mixed evenly, heated to 180 °C for reaction for 3 h, and then crushed and sieved to obtain a P-doped precursor; (2) pre-carbonizing the P-doped precursor product obtained in step (1) at 400° C. for 2 h under a nitrogen atmosphere, then cooling to room temperature, and pulverizing to obtain a P-doped pre-carbonized precursor; (3) mixing 1 g of graphene oxide with 1 liter of water and performing ultrasonic dispersion for 5 hours to obtain a graphene oxide dispersion; (4) The graphene oxide dispersion of step (3) was transferred to a constant temperature water bath at 85° C., 1000 g of P-doped pre-carbonized precursor was added during stirring, 15 g of ferric nitrate was added after stirring for 6 hours, and stirring was continued for 1 hour to obtain a suspension, the suspension was filtered, washed with pure water, and dried to obtain a graphene-coated P-doped pre-carbonized precursor; (5) placing the graphene-coated P-doped pre-carbonized precursor of step (4) in a rotary kiln, and introducing ethane at a flow rate of 2 L / min for 1 h in a nitrogen atmosphere at a flow rate of 100 L / min and an environment of 800° C. to generate carbon nanotubes, then switching to introducing nitrogen, and naturally cooling to room temperature to obtain material 1; (6) Material 1 is placed in a high-temperature furnace and carbonized at 1000°C for 6 hours under a nitrogen atmosphere. After cooling to room temperature, material 2 is obtained; (7) Material 2 was soaked in a hydrochloric acid solution with a pH of 3 for 1 hour, and finally washed with deionized water until neutral and dried to obtain the hard carbon composite negative electrode material.
[0040] The prepared hard carbon composite negative electrode material has a core-shell structure, which includes a core, an inner shell and an outer shell, wherein the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell, wherein the core is hard carbon containing P and graphite microcrystals, the inner shell is graphene, and the outer shell is carbon nanotubes. The thickness of the outer shell is 7nm, and the thickness of the inner shell is 20nm.
[0041] Example 3 A high-rate, high-initial-effect biomass hard-carbon composite negative electrode material, the preparation method of which comprises the following steps: (1) 100 g coconut shell and 20 g phosphoric acid were mixed evenly, heated to 180 °C for 4 h, and crushed and sieved to obtain a P-doped precursor; (2) pre-carbonizing the P-doped precursor product obtained in step (1) at 500° C. for 2 h in a nitrogen atmosphere, cooling it to room temperature, and then pulverizing it to obtain a P-doped pre-carbonized precursor; (3) mixing 1.5 g of sulfonated graphene with 1 liter of water and performing ultrasonic dispersion for 4 hours to obtain a sulfonated graphene dispersion; (4) The sulfonated graphene dispersion of step (3) was transferred to a constant temperature water bath at 85°C, 1000 g of P-doped pre-carbonized precursor was added under stirring, 45 g of ferric nitrate was added after stirring for 6 hours, and stirring was continued for 2 hours to obtain a suspension, the suspension was filtered, washed with pure water, and dried to obtain a graphene-coated P-doped pre-carbonized precursor; (5) placing the graphene-coated P-doped pre-carbonized precursor of step (4) in a rotary kiln, and introducing ethane at a flow rate of 1 L / min for 2 h in a nitrogen atmosphere at a flow rate of 80 L / min and a temperature of 700 ° C to generate carbon nanotubes, then switching to introducing nitrogen, and naturally cooling to room temperature to obtain material 1; (6) Material 1 is placed in a high-temperature furnace and carbonized at 1400°C for 5 h under a nitrogen atmosphere. After cooling to room temperature, material 2 is obtained; (7) Material 2 was soaked in a hydrochloric acid solution with a pH of 4 for 1 hour, and finally washed with deionized water until neutral and dried to obtain the hard carbon composite negative electrode material.
[0042] The prepared hard carbon composite negative electrode material has a core-shell structure, the core-shell structure includes a core, an inner shell and an outer shell, the inner shell is coated on the surface of the core, the outer shell is coated on the surface of the inner shell, the core is hard carbon containing P and graphite microcrystals, the inner shell is graphene, and the outer shell is carbon nanotubes. The thickness of the outer shell is 10nm, and the thickness of the inner shell is 25nm.
[0043] Example 4 A high-rate, high-initial-effect biomass hard-carbon composite negative electrode material, the preparation method of which comprises the following steps: (1) 100 g coconut shell and 6 g phosphoric acid were mixed evenly, heated to 160 °C for 4 h, and crushed and sieved to obtain a P-doped precursor; (2) pre-carbonizing the P-doped precursor product obtained in step (1) at 600° C. for 2 h in a nitrogen atmosphere, cooling it to room temperature, and then pulverizing it to obtain a P-doped pre-carbonized precursor; (3) Mixing 1 g of sulfonated graphene with 1 liter of water and performing ultrasonic dispersion for 2 hours to obtain a sulfonated graphene dispersion; (4) The sulfonated graphene dispersion of step (3) was transferred to a constant temperature water bath at 85°C, 1000 g of P-doped pre-carbonized precursor was added under stirring, 12 g of ferric nitrate was added after stirring for 6 hours, and stirring was continued for 2 hours to obtain a suspension, and the suspension was filtered, washed with pure water, and dried to obtain a graphene-coated P-doped pre-carbonized precursor; (5) placing the graphene-coated P-doped pre-carbonized precursor of step (4) in a rotary kiln, and introducing ethane at a flow rate of 1 L / min for 1 h in a nitrogen atmosphere at a flow rate of 70 L / min and an environment of 800° C. to generate carbon nanotubes, then switching to introducing nitrogen, and naturally cooling to room temperature to obtain material 1; (6) placing material 1 in a high-temperature furnace, carbonizing it at 1200°C for 5 h under a nitrogen atmosphere, and cooling it to room temperature to obtain material 2; (7) Material 2 was soaked in a hydrochloric acid solution with a pH of 4 for 1 hour, and finally washed with deionized water until neutral and dried to obtain the hard carbon composite negative electrode material.
[0044] The prepared hard carbon composite negative electrode material has a core-shell structure, which includes a core, an inner shell and an outer shell, wherein the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell, wherein the core is hard carbon containing P and graphite microcrystals, the inner shell is graphene, and the outer shell is carbon nanotubes. The thickness of the outer shell is 5 nm, and the thickness of the inner shell is 12 nm.
[0045] Comparative Example 1 A hard carbon composite negative electrode material, the preparation method of which comprises the following steps: (1) 100 g of fruit shell and 15 g of phosphoric acid were mixed evenly, heated to 160 °C for 4 h, and crushed and sieved to obtain a P-doped precursor; (2) pre-carbonizing the P-doped precursor product obtained in step (1) at 500° C. for 2 h in a nitrogen atmosphere, cooling it to room temperature, and then pulverizing it to obtain a P-doped pre-carbonized precursor; (3) mixing 1.2 g of sulfonated graphene with 1 liter of water and performing ultrasonic dispersion for 4 hours to obtain a sulfonated graphene dispersion; (4) The sulfonated graphene dispersion of step (3) was transferred to a constant temperature water bath at 85°C, 1000 g of P-doped pre-carbonized precursor was added under stirring, 30 g of ferric nitrate was added after stirring for 6 hours, and stirring was continued for 2 hours to obtain a suspension, and the suspension was filtered, washed with pure water, and dried to obtain a graphene-coated P-doped pre-carbonized precursor; (5) placing the graphene-coated P-doped pre-carbonized precursor of step (4) in a high-temperature furnace, carbonizing it at 1200° C. for 5 h in a nitrogen atmosphere, and cooling it to room temperature to obtain material 2; (6) The material 2 of step (5) is soaked in a hydrochloric acid solution with a pH of 3 for 1 hour, and finally washed with deionized water until it is neutral and dried to obtain the hard carbon composite negative electrode material.
[0046] The prepared hard carbon composite negative electrode material has a core-shell structure, which includes a core and an outer shell, wherein the core is hard carbon containing P and graphite microcrystals, and the outer shell is graphene, and the thickness of the outer shell is 22 nm.
[0047] Comparative Example 2 A hard carbon composite negative electrode material, the preparation method of which comprises the following steps: (1) 100 g of fruit shell and 15 g of phosphoric acid were mixed evenly, heated to 160 °C for 4 h, and crushed and sieved to obtain a P-doped precursor; (2) pre-carbonizing the P-doped precursor product of step (1) at 500° C. for 2 h in a nitrogen atmosphere, cooling to room temperature, and then pulverizing to obtain a P-doped pre-carbonized precursor; (3) mixing 1.2 g of sulfonated graphene with 1 liter of water and performing ultrasonic dispersion for 4 hours to obtain a sulfonated graphene dispersion; (4) The sulfonated graphene dispersion of step (3) was transferred to a constant temperature water bath at 85°C, 1000 g of P-doped pre-carbonized precursor was added under stirring, and a suspension was obtained after stirring for 6 hours. The suspension was filtered, washed with pure water, and dried to obtain a graphene-coated P-doped pre-carbonized precursor; (5) Placing the graphene-coated P-doped pre-carbonized precursor of step (4) in a high-temperature furnace, carbonizing it at 1200° C. for 5 h in a nitrogen atmosphere, and cooling it to room temperature to obtain the hard carbon composite negative electrode material.
[0048] The prepared hard carbon composite negative electrode material has a core-shell structure, wherein the core-shell structure comprises a core and an outer shell, wherein the core is hard carbon containing P, and the outer shell is graphene, and the thickness of the outer shell is 22 nm.
[0049] Comparative Example 3 A hard carbon composite negative electrode material, the preparation method of which comprises the following steps: (1) 100 g of fruit shell and 15 g of phosphoric acid were mixed evenly, heated to 160 °C for 4 h, and crushed and sieved to obtain a P-doped precursor; (2) pre-carbonizing the P-doped precursor product obtained in step (1) at 500° C. for 2 h in a nitrogen atmosphere, cooling it to room temperature, and then pulverizing it to obtain a P-doped pre-carbonized precursor; (3) adding 1000 g of the P-doped pre-carbonized precursor and 30 g of ferric nitrate from step (2) to 1 L of water, stirring for 6 hours, and then adding 30 g of ferric nitrate to obtain a suspension, filtering the suspension, washing with pure water, and drying to obtain a P-doped pre-carbonized precursor; (4) placing the P-doped pre-carbonized precursor of step (3) in a rotary kiln, and introducing acetylene at a flow rate of 1 L / min for 6 hours in a nitrogen atmosphere at a flow rate of 100 L / min and an environment of 600°C to generate carbon nanotubes, then switching to introducing nitrogen, and naturally cooling to room temperature to obtain material 1; placing material 1 in a high-temperature furnace, carbonizing it at 1200°C for 5 hours in a nitrogen atmosphere, and cooling it to room temperature to obtain material 2; (5) The material 2 of step (4) is soaked in a hydrochloric acid solution with a pH of 3 for 1 hour, and finally washed with deionized water until it is neutral and dried to obtain the hard carbon composite negative electrode material.
[0050] The prepared hard carbon composite negative electrode material has a core-shell structure, which includes a core and an outer shell. The core is hard carbon containing P and graphite microcrystals, and the outer shell is a carbon nanotube. The thickness of the outer shell is 6 nm.
[0051] Comparative Example 4 A hard carbon composite negative electrode material, the preparation method of which comprises the following steps: (1) 100 g of fruit shell and 15 g of phosphoric acid were mixed evenly, heated to 160 °C for 4 h, and crushed and sieved to obtain a P-doped precursor; (2) pre-carbonizing the P-doped precursor product of step (1) at 500° C. for 2 h in a nitrogen atmosphere, cooling to room temperature, and then pulverizing to obtain a P-doped pre-carbonized precursor; (3) adding 1000 g of the P-doped pre-carbonized precursor and 30 g of ferric nitrate from step (2) to 1 L of water, stirring for 6 hours, and then adding 30 g of ferric nitrate to obtain a suspension, filtering the suspension, washing with pure water, and drying to obtain a P-doped pre-carbonized precursor; (4) The P-doped pre-carbonized precursor of step (3) is placed in a high-temperature furnace and carbonized at 1200°C for 5 h in a nitrogen atmosphere. After cooling to room temperature, it is immersed in a hydrochloric acid solution with a pH of 3 for 1 h. Finally, it is washed with deionized water until it is neutral and dried to obtain hard carbon containing P and graphite microcrystals.
[0052] Performance Testing The hard carbon composite negative electrode materials prepared in the above Examples 1-4 and Comparative Examples 1-4 were used as negative electrode materials for sodium ion batteries, and electrochemical performance tests were performed as follows: The hard carbon composite negative electrode material, conductive agent Super P, binder sodium carboxymethyl cellulose (CMC) and aqueous binder (SBR) of each example were weighed in a mass ratio of 95:2:1.5:1.5, and after being fully ground in an agate mortar, a small amount of deionized water was added to form a uniform black paste slurry. The slurries were coated on the copper foil current collector as the test electrode, and the metal sodium sheet was used as the comparison electrode to assemble into a button cell. Among them, the electrolyte is 1M sodium hexafluorophosphate dissolved in a mixed solution of ethylene carbonate (EC) and dimethyl carbonate (DMC) with a volume ratio of 1:1, and 5wt.% of fluoroethylene carbonate (FEC) was added to the electrolyte as an additive; glass fiber was used as a separator; CR2032 stainless steel was used as a battery shell to assemble into a button cell. The obtained button cell was tested for capacity and first coulomb efficiency at a constant rate of 0.1C in the voltage range of 0.01 to 3.0 V.
[0053] The hard carbon composite negative electrode material prepared in Examples 1-4 and Comparative Examples 1-4 was used as the negative electrode, sodium nickel iron manganese oxide was used as the positive electrode, and 1M-NaPF6+EC:DEC:DMC (volume ratio 1:1:1) solution was used as the electrolyte. The cells were assembled into full batteries in a stacked manner and charged and discharged at room temperature at a rate of 1C, with a voltage range of 1.5-3.9V.
[0054] Rate performance test: Under normal temperature conditions, the prepared battery was tested on the LAND battery test system, and the specific capacity of the battery was tested at current densities of 0.1A / g, 0.2A / g, 0.5A / g, 1A / g, 2A / g, and 5A / g. The test results are shown in Table 1.
[0055] Table 1 Electrochemical properties of hard carbon composite negative electrode materials of Examples 1-4 and Comparative Examples 1-4
[0056] It can be seen from the test results in Table 1 that, compared with Comparative Examples 1-4, the hard carbon composite negative electrode material prepared by the present invention has high initial charge and discharge efficiency, cycle performance and rate performance.
[0057] Comparative Example 1 is compared with Example 1. Chemical vapor deposition is not performed in Comparative Example 1. The hard carbon composite negative electrode material obtained has a core-shell structure, in which the core is hard carbon containing P and graphite microcrystals, and the shell is graphene. During the high-temperature carbonization process of Comparative Example 1, graphene and the transition metal on its surface synergistically induce the hard carbon to grow along the graphene layer, and there is a chemical bond between the graphene coating layer and the hard carbon, so that the graphene coating layer can be tightly coated on the hard carbon surface. However, since there are no carbon nanotubes on the surface of the graphene coating layer of Comparative Example 1, graphene is easily piled up during the charge and discharge process, resulting in a slight decrease in the negative electrode cycle performance.
[0058] Comparative Example 2 is compared with Example 1 and Comparative Example 1. No transition metal ions are added to Comparative Example 2, and no chemical vapor deposition is performed. During the high-temperature carbonization process of Comparative Example 2, graphene induces hard carbon to grow along the graphene layer, but without the synergistic effect of transition metal ions, the chemical bond between the coating layer and the hard carbon becomes weak, and the graphene easily falls off during the charge and discharge process, resulting in a significant reduction in the negative electrode cycle performance. In addition, there is no transition metal ion catalytic graphitization on the surface of the coating layer, and the atomic arrangement of the generated graphene coating layer is irregular, and the graphene coating layer has many defects, which reduces the first coulomb efficiency of the composite negative electrode material. In addition, phosphorus doping widens the hard carbon interlayer spacing and improves the sodium ion insertion / extraction kinetics; however, there is no catalytic graphitization of transition metal ions, and no graphite crystals are generated inside the hard carbon material. Only graphene is used to improve the electron transfer kinetics, and the rate performance of the hard carbon material is reduced.
[0059] Comparative Example 3 is compared with Example 1, and graphene is not added in the preparation process of Comparative Example 3. During the high-temperature carbonization process, although the transition metal and carbon nanotubes can also induce the hard carbon to grow along the carbon nanotube layer, so that there is a chemical bond between the carbon nanotube coating layer and the hard carbon, the carbon nanotube is in a round tube shape, and the formed coating layer has a poor bonding force with the hard carbon, which is easy to fall off during the charge and discharge process, and easily causes a decrease in the cycle performance of the negative electrode material.
[0060] Comparing Comparative Example 4 with Example 1, Comparative Example 4 only adds transition metals. During the high-temperature carbonization process, the transition metal ions catalyze graphitization, so that graphite crystals are generated inside the hard carbon material. However, without the graphene and carbon nanotube coating layers, the first coulomb efficiency, cycle performance and rate performance of the negative electrode material are all low.
[0061] In summary, the present invention coats a graphene layer on the surface of biomass hard carbon, and in situ grows carbon nanotubes on the graphene surface. During the high-temperature carbonization process, the transition metal synergistically induces the hard carbon to grow along the graphene layer, enhances the chemical bond between the coating layer and the hard carbon, and makes the graphene coating layer tightly coated, thereby improving the material's cycle performance; the transition metal ions catalyze graphitization to generate a more regular and orderly graphite-like microcrystalline structure coating layer, reduce the defects of graphene and carbon nanotubes, and improve the material's first coulomb efficiency; in addition, phosphorus doping improves the ion transmission capacity, and the graphite microcrystals catalytically generated inside the hard carbon improve the electron transmission capacity. The synergistic improvement of ion transmission and electron transmission ensures the material's rate performance. Therefore, the present invention effectively overcomes the various shortcomings of the prior art and has a high industrial utilization value.
[0062] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a high-rate, high-initial-efficiency biomass hard carbon composite negative electrode material, characterized in that: The steps include: (1) After the biomass raw material and phosphoric acid are uniformly mixed, they are heated to react for a period of time, and then crushed and sieved to obtain a P-doped precursor; (2) pre-carbonizing the P-doped precursor obtained in step (1), cooling it to room temperature, and pulverizing it to obtain a P-doped pre-carbonized precursor; (3) mixing graphene with water and performing ultrasonic dispersion to obtain a graphene dispersion; (4) transferring the graphene dispersion of step (3) into a constant temperature water bath, adding a P-doped pre-carbonized precursor and a transition metal salt to obtain a suspension, filtering, washing, and drying the suspension to obtain a graphene-coated P-doped pre-carbonized precursor; (5) chemically vapor depositing the graphene-coated P-doped pre-carbonized precursor of step (4) with a carbon source to obtain material 1; (6) placing the material 1 of step (5) in a high temperature furnace for high temperature carbonization treatment, and cooling to room temperature to obtain material 2; (7) The material 2 obtained in step (6) is soaked in an acid solution, and finally washed with deionized water until it is neutral and dried to obtain the hard carbon composite negative electrode material.
2. The preparation method according to claim 1, characterized in that: In step (1), the biomass raw material includes at least one of lychee wood, apple wood, poplar wood, bamboo, fruit shell, straw, coconut shell and corn cob.
3. The preparation method according to claim 1, characterized in that: In step (1), the biomass raw material and phosphoric acid are mixed and heated to 150°C-200°C for reaction for 1-6 hours.
4. The preparation method according to claim 1, characterized in that: In step (2), the pre-carbonization treatment is: pre-carbonizing the P-doped precursor at 300° C.-600° C. for 1-6 hours in a nitrogen atmosphere.
5. The preparation method according to claim 1, characterized in that: The graphene includes at least one of sulfonated graphene and graphene oxide; the mass ratio of the graphene to the P-doped pre-carbonized precursor is (0.1-0.4):
100.
6. The preparation method according to claim 1, characterized in that: In step (4), the transition metal salt includes at least one of nitrates, chlorides, sulfates, acetates and oxalates of transition metals; and the transition metal is at least one of iron, cobalt, nickel and chromium.
7. The preparation method according to claim 6, characterized in that: In step (4), the mass ratio of the transition metal salt to the P-doped pre-carbonized precursor is (1-5):
100.
8. The preparation method according to claim 1, characterized in that: In step (6), the high temperature carbonization treatment is as follows: placing material 1 in a high temperature furnace and carbonizing it at 900°C-1400°C for 1-6 hours in a nitrogen atmosphere.
9. A hard carbon composite negative electrode material prepared by the preparation method as described in any one of claims 1 to 8, wherein the hard carbon composite negative electrode material has a core-shell structure, the core-shell structure includes a core, an inner shell and an outer shell, the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell; the core includes biomass hard carbon containing P and graphite crystals, the inner shell includes graphene, and the outer shell includes carbon nanotubes.
10. An application of a hard carbon composite negative electrode material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The hard carbon composite negative electrode material is used as the negative electrode material of a sodium ion battery.
Citation Information
Patent Citations
Three-dimensional network graphene with biomass structure and preparation method thereof
CN111424257A
MOx / hard carbon / rGO negative electrode material for sodium ion battery and preparation method of MOx / hard carbon / rGO negative electrode material
CN116247211A
Preparation method of lignin-based hard carbon for sodium ion battery
CN118637591A
Negative active material and preparation method thereof, negative pole piece and secondary battery
CN118738386A
Sodium-ion battery negative electrode material, preparation method thereof and sodium-ion battery
CN118782768A
Cited By
Graphene coated hard carbon negative electrode material and preparation method thereof
CN119660717A
Graphene-Coated Hard Carbon Anode Material and Its Preparation Method
CN119660717B
Graphite composite material, preparation method thereof and application of graphite composite material in lithium ion battery
CN119852375A
High-power artificial graphite as well as preparation method and application thereof
CN119976824A
Multilayer composite antioxidant copper foil and manufacturing process thereof
CN120534028A
